The injury workforce in Western Australia: Findings from a cross-sectional survey - Jancey, Jonine; Crawford, Gemma; Hunt, Kristen; Wold, Catrina; Leavy, Justine; Hallett, Jonathan (WILEY, 2019)
Issue addressed: Since 1986, injury prevention and control has been classified as a National Health Priority. However, no reviews into the injury prevention workforce have been conducted in Australia since 2011 and to date; none has focused specifically on the injury prevention and safety promotion sector in Western Australia (WA). This research sought to review the scope of the injury prevention and safety promotion workforce in WA to gain a greater understanding of sector characteristics, work and needs. Methods: An online, cross-sectional survey was conducted between mid-January and mid-March 2018. Participants were required to be: (a) based in WA or have a program running within WA; and (b) working in injury prevention and safety promotion relating to programs, policy or legislation development, implementation and/or evaluation within intentional (eg interpersonal violence, suicide and self-harm) or unintentional injuries (eg transport, poisoning, falls, drowning, burns) or farm, child and community, occupational health and safety, sport and recreation and trauma. Results: The research found that participants were predominantly female (82%), aged 40 years or older (66.1%) and were employed full time (55.6%). The majority of participants worked in falls prevention (38.5%), alcohol and other drugs (38.0%), injury in general (31.8%) and community safety (30.7%). Conclusions: Findings demonstrate significant heterogeneity with a core workforce supported by a range of non-core and indirect actors. Identifying characteristics and needs of the workforce supports coordinated capacity building to implement effective injury prevention and safety promotion initiatives. With this being the first review of the workforce in WA, this article highlights the need to more regularly audit the sector to determine its breadth and composition. So what?: In the light of the recent announcement by the Commonwealth for a new national Injury Prevention Strategy, this study provides timely insights into the injury prevention and safety promotion sector in WA.